Reconstructing the Gravitational Hologram with Quantum Information - AAVV (Il Colle di Galileo, 2024)
Maldacena’s 1997 discovery of gauge/gravity duality promised to provide a complete understanding of quantum effects in gravity, by relating gravitating quantum systems to conventional quantum field theories on fixed backgrounds. Although much has been learned, this initial promise has not been completely fulfilled, due to lingering questions associated with the basic dictionary describing the way observables are mapped between one description and the other. While the dictionary is under good control for observables near the boundary, and also at the level of perturbation theory about a classical bulk spacetime for observables further in, non-perturbative questions critical for a full resolution of the black hole information problem remain to be fully answered. Over the last few years, however, a number of developments arising from the application of quantum information theory to AdS/CFT seem to be indicating that it may now be possible to address some of these questions. This GGI workshop brought together experts and young researchers, in order to capitalize on these developments.